2022
DOI: 10.1093/nutrit/nuac058
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary patterns and depression: an umbrella review of meta-analyses of observational studies and intervention trials

Abstract: Context Depression is the most common causes of disease burden worldwide (GBD 2017 Disease and Injury Incidence and Prevalence Collaborators. Global, regional, and national incidence, prevalence, and years lived with disability for 354 diseases and injuries for 195 countries and territories, 1990–2017: a systematic analysis for the Global Burden of Disease Study 2017. Lancet. 2018;392:1789–1858). Objective An umbrella review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 69 publications
2
19
1
Order By: Relevance
“…The Mediterranean diet (MD) is promoted as one of the healthiest dietary patterns for preventing non-communicable diseases (NCDs), including conditions involving cognitive impairment and mental illness [11,12]. These beneficial effects may be linked to the high consumption of plant-based products rich in polyphenols and vitamins, which are essential for brain function [13].…”
Section: Introductionmentioning
confidence: 99%
“…The Mediterranean diet (MD) is promoted as one of the healthiest dietary patterns for preventing non-communicable diseases (NCDs), including conditions involving cognitive impairment and mental illness [11,12]. These beneficial effects may be linked to the high consumption of plant-based products rich in polyphenols and vitamins, which are essential for brain function [13].…”
Section: Introductionmentioning
confidence: 99%
“…Among the recommended diet for reducing depression risk are fruits, vegetables, legumes, wholegrain cereals, and nuts instead of unhealthy products such as fast foods, pastries, and soft drinks [ 53 ]. Despite the fact that existing evidence on DQ only discussed certain kinds of food, the healthy dietary pattern in our study is comprehensive enough to cover the aforementioned nutrients, whose potential positive impact on depression symptoms is worthy of prompt replication in larger populations [ 54 ]. As well-documented as either the single effect of diet or PA alone for preventing depression is, there are no relevant studies that have examined the effects of diet and PA as a whole on depression.…”
Section: Discussionmentioning
confidence: 99%
“…The Mediterranean diet is characterized by a high intake of vegetables, fruits and nuts, legumes, olive oils, and fish as well as reduced consumption of meat and dairy products with moderate alcohol intake (Altun et al, 2019; Sánchez-Villegas et al, 2006). Several cohort and cross-sectional studies (Gibson-Smith et al, 2018; Sánchez-Villegas et al, 2015), meta-analyses (Lassale et al, 2019; Psaltopoulou et al, 2013), and recent systematic reviews (Altun et al, 2019; Gianfredi et al, 2022) have indicated that moderate to high adherence to the Mediterranean diet significantly reduces risk for depressive symptoms. Furthermore, the first randomized control trial exploring a dietary intervention for treatment of depression found that a modified Mediterranean diet decreased depressive symptoms (Jacka et al, 2017).…”
Section: Research On Nutrition and Depressionmentioning
confidence: 99%